43.2k views
4 votes
Solve the system of equations for the variables: x+2y-z=3 x+y-2z= -1

2 Answers

1 vote

Explanation:

x + 2y − z = 3

x + y − 2z = -1

There are three variables but only two equations, so this system of equations is undefined. We cannot solve for the variables, but we can eliminate one of them and reduce this to a single equation.

Double the first equation:

2x + 4y − 2z = 6

Subtract the second equation.

(2x + 4y − 2z) − (x + y − 2z) = (6) − (-1)

2x + 4y − 2z − x − y + 2z = 7

x + 3y = 7

User Bignum
by
4.6k points
7 votes

Answer:

z=0

x= -5

y=4

Explanation:

Check the attachment please

Hope this helps :)

Solve the system of equations for the variables: x+2y-z=3 x+y-2z= -1-example-1
User Reed Morse
by
4.8k points